Circulating peptide YY concentrations are higher in preterm than full-term infants and correlate negatively with body weight and positively with serum ghrelin concentrations. - Tania Siahanidou; Mandyla, Helen; Vounatsou, Maria; Anagnostakis, Dimitris; Papassotiriou, Ioannis; Chrousos, George P (Clin Chem, 2005)
BACKGROUND: Peptide YY (PYY) and ghrelin are gastrointestinal tract-derived hormones that play roles in the regulation of food intake and energy balance. Negative energy balance often occurs in hospitalized preterm infants. METHODS: To measure serum concentrations of PYY in preterm and full-term infants and to investigate their correlations with anthropometric characteristics, food intake, and serum ghrelin concentrations, we measured serum PYY and ghrelin concentrations by RIA in 62 healthy preterm infants [mean (SD) gestational age, 32.0 (2.1) weeks; postnatal age, 40.9 (14.8) days] and 15 healthy full-term infants of comparable postnatal age. All of the infants were formula-fed every 3 h. RESULTS: PYY concentrations were significantly higher in preterm [1126.2 (215.4) ng/L] than in full-term infants [825.3 (234.4) ng/L; P < 0.001]. In the entire study population, serum PYY concentrations correlated negatively with gestational age and anthropometric measurements (birth weight, body weight, body length, body mass index, and head circumference) and positively with serum ghrelin concentrations, whereas there was no significant correlation between PYY concentration and caloric intake or weight gain. Multiple regression analysis, after correction for prematurity, revealed that serum PYY concentrations correlated independently with serum ghrelin concentrations and infant body weight or body mass index. CONCLUSIONS: Circulating concentrations of PYY may increase in preterm infants to compensate for the negative body-weight balance. The physiologic mechanisms behind the correlation between PYY and ghrelin remain to be elucidated.
Keywords: Anthropometry; Body Weight; Gestational Age; Ghrelin; Humans; Infant; Newborn; Peptide Hormones; Peptide YY; Premature; Regression Analysis